Efeitos de uma desintegrina RGD recombinante de Rhinocerophis alternatus (Bothrops alternatus) na migração de células normais e tumorais - Montenegro, Cyntia de Freitas (2011)
Cell migration, invasion of the surrounding tissues, blood vessels and proliferation are cellular processes involved in metastases. These events are mediated by integrins, adhesion receptors present on cell surfaces and responsible for the extracellular matrix and cells binding. Disintegrins, snake venoms polypeptides, are known to inhibit integrins action, and thus metastatic events such as cell migration. They also have influence on metallopeptidases activity, enzymes that cleave ECM components facilitating tumor cells invasion. DisBa-01 is a recombinant RGD disintegrin from Rhinocerophis alternatus (Bothrops alternatus) venom gland. In previous studies we have demonstrated that DisBa-01 binds to _v_3 integrin with high affinity and has an anti-metastatic activity. Therefore the aim of this study was to investigate the effect of DisBa-01 on migration and MMPs activities in fibroblasts and cell lines of breast cancer, MDA-MB-231, prostate, DU-145 and murine melanoma, B16F10. Transwell migration tests, wound healing and gelatin gel zymography were performed using DisBa-01 at concentrations of 10, 100, 500 and 1000 nM. Transwell migration was significantly inhibited in fibroblasts, MDA-MB-231 and DU-145 but had no effect on B16F10 cells, which had fibroblast conditioned medium as chemoattractant. In wound healing assays only DU-145 migration in a 1000nM concentration was significantly inhibited. Finally, zymography was performed using wound healing assay conditioned medium to analyze the presence of MMPs 2 and 9. In fibroblasts and B16F10 cells MMP-2 and MMPs 2 and 9 were decreased respectively. On the other hand, MDA-MB-231 cells showed increased MMP-9 activity, in all concentrations tested. Given the results, DisBa-01 can be used to build models for possible drugs rational design that may act in anti-metastatic therapy, in addition to its use as a research tool to elucidate integrins related mechanisms.